Air processed Cs2AgBiBr6 lead‑free double perovskite high‑mobility thin‑flm feld‑efect transistors - Abiram, G.; HeidariGourji, F.; Pitchaiya, S.; Ravirajan, P.; Murugathas, T.; Velauthapillai, D. (Scientifc Reports, 2022)
This study focuses on the fabrication and characterization of Cs2AgBiBr6 double perovskite thin flm for feld-efect transistor (FET) applications. The Cs2AgBiBr6 thin flms were fabricated using a solution process technique and the observed XRD patterns demonstrate no difraction peaks of secondary phases, which confrm the phase-pure crystalline nature. The average grain sizes of the spin-deposited flm were also calculated by analysing the statistics of grain size in the SEM image and was found to be around 412 (± 44) nm, and larger grain size was also confrmed by the XRD measurements. FETs with diferent channel lengths of Cs2AgBiBr6 thin flms were fabricated, under ambient conditions, on heavily doped p-type Si substrate with a 300 nm thermally grown SiO2 dielectric. The fabricated Cs2AgBiBr6 FETs showed a p-type nature with a positive threshold voltage. The on-current, threshold voltage and hole-mobility of the FETs decreased with increasing channel length. A high average hole mobility of 0.29 cm2 s−1 V−1 was obtained for the FETs with a channel length of 30 µm, and the hole-mobility was reduced by an order of magnitude (0.012 cm2 s−1 V−1) when the channel length was doubled. The on-current and hole-mobility of Cs2AgBiBr6 FETs followed a power ft, which confrmed the dominance of channel length in electrostatic gating in Cs2AgBiBr6 FETs. A very high-hole mobility observed in FET could be attributed to the much larger grain size of the Cs2AgBiBr6 flm made in this work.